The reduction of chloride ion concentration in basal ice near Hamna Icefall, East Antarctica - イイズカ, ヨシノリ; サタケ, ヒロシ; ワタナベ, オキツグ; Iizuka, Yoshinori; Satake, Hiroshi; Watanabe, Okitsugu (National Institute of Polar Research, 2001)
P(論文) The present paper mainly discusses chloride ions (Cl^-) in debris-laden basal ice near Hamna Icefall, Queen Maud Land, East Antarctica. The basal ice consists of alternating layers of bubble-free and bubbly ice of the order of mm to cm in thickness. Detailed analyses of Cl^- and stable isotopes (δ^<18>O and δD) on the alternating layers were performed. The Cl^- concentrations in the bubble-free ice layers and in the bubbly ice layers whose isotopic fluctuations decrease from neighboring bubble-free ice layers are reduced compared to those in the bubbly ice layers having quasi-neutral values on the isotopic profile. The reduction of Cl concentration in frozen ice compared to that in pre-freezing water was also observed from an experiment on ion fractionation by freezing. These results suggest that the bubble-free ice layers and the bubbly ice layers whose isotopic fluctuation is decreased from that in neighboring bubble-free ice layers were formed by melt-refreezing processes. The reduction of Cl concentration in the basal ice is considered to be an indicator to distinguish whether the basal ice has experienced melt-refreezing or not. departmental bulletin paper